Clostridium acetobutylicum Biofilm: Advances in Understanding the Basis - Zhang, Huifang; Yang, Pengpeng; Wang, Zhenyu; Li, Mengting; Zhang, Jie; Liu, Dong; Chen, Yong; Ying, Hanjie (Frontiers in Bioengineering and Biotechnology, 2021)
Clostridium acetobutylicum is an important industrial platform capable of producing a variety of biofuels and bulk chemicals. Biofilm of C. acetobutylicum renders many production advantages and has been long and extensively applied in fermentation. However, molecular and genetic mechanisms underlying the biofilm have been much less studied and remain largely unknown. Here, we review studies to date focusing on C. acetobutylicum biofilms, especially on its physiological and molecular aspects, summarizing the production advantages, cell physiological changes, extracellular matrix components and regulatory genes of the biofilm. This represents the first review dedicated to the biofilm of C. acetobutylicum. Hopefully, it will deepen our understanding toward C. acetobutylicum biofilm and inspire more research to learn and develop more efficient biofilm processes in this industrially important bacterium.